Histopathological study of canine hepatoid gland tumours - P.M. Shabeeba (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 2021)
Hepatoid gland neoplasms arise due to disorganized and uncontrolled proliferation of cells of hepatoid glands. These are the modified sebaceous glands located mainly in the perianal area. Gross and histological findings of canine hepatoid gland tumours were evaluated. Dogs of different breed, age and sex that were presented to Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Sciences, Mannuthy formed the materials for the present study. Grossly, tumours were solitary or multiple irregular shaped intradermal masses. The excisional biopsy samples were collected in 10 per cent neutral buffered formalin after surgical removal of tumour mass. Histopathologically, the masses were encircled by fibrovascular capsule which extended to the parenchyma as tumour stroma, which separated it into lobules. Two cases of hepatoid gland adenoma one case of hepatoid gland epithelioma and two cases of carcinoma were recognised on histopathological examination. Hepatoid adenoma were characterised by proliferation of hepatocyte like hepatoid gland epithelial cells with extensive sebaceous differentiation and were arranged in cords and anastomosing trabeculae. In hepatoid gland epithelioma, many of the cells were basaloid reserve cells with fewer hepatocyte like cells. Histopathological examination of carcinoma revealed irregular arrangement of the hepatoid cells which showed varying degrees of maturation and marked nuclear pleomorphism. The malignant hepatoid cells had abundant eosinophilic cytoplasm and large nuclei with several prominent nucleoli and mitotic figures.